Advanced low-temperature ceramic nanocomposite fuel cells using ultra high ionic conductivity electrolytes synthesized through freeze-dried method and solid-route. (September 2017) - Asghar, Muhammad Imran; Heikkilä, Mikko; Lund, Peter D.
Abstract: Low ionic conductivity and slow reaction kinetics often limit the performance of a ceramic nanocomposite fuel cell (CNFC). Here, we report a novel synthesis method, freeze-dried method, to achieve a record high ionic conductivity for nanocomposite electrolytes (>0.5 S/cm) based on Ce0.85 Sm0.15 O2 (SDC) and a eutectic mixture of Na2 CO3, Li2 CO3, K2 CO3 (NLK). The highest ionic conductivity (0.55 S/cm) was reached by increasing the carbonate content of the electrolyte to 35 wt%. For the sake of comparison, the nanocomposite electrolytes were also prepared through solid-route. Composite anodes and cathodes for complete fuels were prepared from NiO and La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF), respectively using both solid-route and freeze-dried nanocomposite electrolytes. Complete fuel cells manufactured from these nanocomposite materials produced ∼1.1 W/cm 2 at 550 °C. The EIS measurements revealed low ohmic losses (0.18 Ω cm 2 ) and even lower charge transfer resistance (0.05 Ω cm 2 ). In addition, it was found that the open-circuit-voltage (OCV) of the CNFCs improved from 1.1 V to 1.2 V when a mixture of air and CO2 was supplied as compared to the case when only air was supplied at the cathode. Finally, high temperature X-ray diffraction (HT-XRD) revealed stable structures of SDC, NiO and LSCF up to 600 °C, which shows the thermal stability of these fuel cell materials. Graphical abstract: Highlights: Nanocomposite electrolytes were synthesized by solid-route and freeze-dried method. Record high ionic conductivity (0.55 S/cm at 600 °C) was achieved for electrolytes. An outstanding performance of 1.1 W/cm 2 was achieved at 550 °C for fuel cells. HT-XRD revealed high thermal stability of anode, cathode and electrolyte materials.